2013
DOI: 10.1136/archdischild-2012-301867
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional voiding in children with asthma

Abstract: A prospective study was performed to evaluate the prevalence of suspected dysfunctional voiding (DV) and associated risk factors in children with asthma. The DV is defined as any voiding symptoms and/or urinary incontinence. Children (4-10-year-old) with asthma (n=178) and healthy subjects (n=197) were enrolled. DV and Incontinence Scoring System were administrated. Demographic features and asthma related characteristics were recorded. Suspected DV was noted in 19 (27.9%) of patients with asthma and 5 (6.6%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In a study conducted on 178 children with asthma, Soyer et al found that 47.1% of those under six years of age had a higher risk of frequent urination. 13 In the present prospective study, conducted as a follow-up to our previous study, logistic regression analysis confirmed that the risk factors of EDOUF include eczema, allergic rhinitis or allergic cough, pruritus (eye rubbing, etc. ), and elevated total serum IgE level.…”
Section: Discussionsupporting
confidence: 84%
“…In a study conducted on 178 children with asthma, Soyer et al found that 47.1% of those under six years of age had a higher risk of frequent urination. 13 In the present prospective study, conducted as a follow-up to our previous study, logistic regression analysis confirmed that the risk factors of EDOUF include eczema, allergic rhinitis or allergic cough, pruritus (eye rubbing, etc. ), and elevated total serum IgE level.…”
Section: Discussionsupporting
confidence: 84%
“…A previous clinical study in our department revealed that children with OAB are often complicated with allergic manifestations, such as eczema, urticaria, skin allergies after mosquito bites, and allergic rhinitis. Soyer et al (10) revealed that the incidence of urgent and frequent urination was higher in asthmatic children. A cross-sectional cohort study involving 101,848 adult males from South Korea demonstrated that asthma was associated with moderate and severe lower urinary tract symptoms (11).…”
Section: Discussionmentioning
confidence: 99%
“…A one-unit increase in age reduced the likelihood of having asthma by 14.8% and the likelihood of GI by 13.8%. In the study conducted by Soyer et al, it was also found that asthma is correlated with the majority of dysfunctional voiding (DV) symptoms in younger children who have completed toilet training, while it is associated with some DV symptoms in older children, such as frequency and urgency [ 26 ]. Our study also revealed that children with GI were younger than children without this condition.…”
Section: Discussionmentioning
confidence: 99%